The epilepsies, EEG and epileptic syndromes - Crespel, Arielle (Montrouge : John Libbey Eurotext, 2019)
Fully revised and updated, this second edition of the second volume of the Atlases of electroencephalography series includes more than 2/3 new high-quality digital figures.A new Classification approach to epileptic seizures and to the epilepsies became official in 2017.
Includes bibliographical references.
Description based on publisher supplied metadata and other sources.
Keywords: Electroencephalography